2014
DOI: 10.1245/s10434-014-4163-y
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Cancer Conferences for Gastrointestinal Malignancies Result in Measureable Treatment Changes: A Prospective Study of 149 Consecutive Patients

Abstract: Background In most jurisdictions, a minority of patients are discussed at multidisciplinary cancer conference (MCC) despite recommendations for such reviews. We assessed the impact of MCC review of gastrointestinal (GI) cancers at a stand-alone cancer center. Methods Patient data were prospectively collected on consecutive cases presented at a GI MCC during a 6-month period. Original treatment plans were collected confidentially before presentation and compared to post-MCC treatment plans. We defined changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 15 publications
1
39
0
1
Order By: Relevance
“…First, it was conducted in a single institution, and results might not be generalizable to other hospitals and geographic areas. However, we reported similar results in a study involving surgeons from all 11 lhin4 hospitals, as did a study at the Roswell Park Cancer Institute involving surgeons participating in a gastrointestinal mcc 13 . Our results are also in line with those of a systematic review of mccs 6 .…”
Section: Discussionsupporting
confidence: 75%
“…First, it was conducted in a single institution, and results might not be generalizable to other hospitals and geographic areas. However, we reported similar results in a study involving surgeons from all 11 lhin4 hospitals, as did a study at the Roswell Park Cancer Institute involving surgeons participating in a gastrointestinal mcc 13 . Our results are also in line with those of a systematic review of mccs 6 .…”
Section: Discussionsupporting
confidence: 75%
“…Results from a first prospective study to evaluate the MDT discussion process and its effects on treatment approaches for a variety of gastrointestinal cancers at a US cancer centre have recently been published [99]. Despite 84% of clinicians being certain of their original plan, a change was recommended in 36% of cases, 72% of which involved major changes; there was 77% adherence to the recommended treatments.…”
Section: Multidisciplinary Teamsmentioning
confidence: 99%
“…A prospective study of an MDT showed that despite 84% of clinicians being certain of their management plan, following the MDT discussion 36% changed their management plan; 72% of these changes were major ones. [22] Furthermore, studies have shown lower survival rates following non-adherence to MDT decisions. [23] Finally, a national CRC registry should be established so that understanding of disease epidemiology, presentation, outcomes and therapeutic resources can be improved.…”
Section: Future Researchmentioning
confidence: 99%